فاعلية استخدام مواقع التواصل الاجتماعي في التعليم لدى طالبات كلية البنات سيئون بجامعة حضرموت - باجري، عادل منصور سالم (جامعة الجزيرة, 2019)
تهدف الدراسة الحالية إلى التعرف على فاعلية استخدام مواقع التواصل الاجتماعي في التعليم لدى طالبات كلية البنات-سيئون بجامعة حضرموت، ولتحقيق هدف الدراسة تم إعداد استبانة تكونت من (٤١) عبارة موزعة ضمن ثلاثة محاور، تم توزيعها على (٤٧) طالبة من طالبات كلية البنات-سيئون في جامعة حضرموت تم اختيارهم بطريقة عشوائية. واستخدام الباحث المنهج الوصفي التحليلي، واتبع الأساليب الإحصائية الملائمة باستخدام الحزمة الإحصائية للعلوم الاجتماعية (SPSS)، وخلصت الدراسة إلى النتائج الآتية. 1-إن درجة استخدام مواقع التواصل الاجتماعي في التعليم جاءت بدرجة أحيانا. 2-إن أهمية استخدام مواقع التواصل الاجتماعي في التعليم جاءت بدرجة غالبا. 3-إن آليات تفعيل مواقع التواصل الاجتماعي في التعليم جاءت بدرجة أحيانا. 4-عدم وجود فروق ذي دلالة إحصائية في درجة استخدام مواقع التواصل الاجتماعي في التعليم تعزى لمتغير الدراسة (التخصص والمستوى). 5-عدم وجود فروق ذي دلالة إحصائية على أهمية استخدام مواقع التواصل الاجتماعي في التعليم تعزى لمتغير الدراسة (التخصص والمستوى). وختمت الدراسة بعدد من التوصيات، أهمها: -نشر ثقافة توظيف مواقع التواصل الاجتماعي بين عناصر المنظومة التعليمية في الجامعات اليمنية. -ضرورة تدعيم دور مواقع التواصل الاجتماعي في رفع كفاءة العملية التعليمية في الجامعات اليمنية. -إنشاء موقع تواصل اجتماعي خاصة بطلبة الجامعات اليمنية، أو مواقع تواصل اجتماعية خاصة لكل جامعة. -ضرورة تطبيق آليات تفعيل مواقع التواصل الاجتماعي في التعليم في الجامعات اليمنية على وجه العموم وجامعة حضرموت على وجه الخصوص. This study aims to know the efficiency of using social media programs for learning process of female students at the college of women-seiyun which belongs to Hadhramout University. In order to achieve the study objectives, the researcher adopted a questionnaire that consists of 41 expressions which have been divided into three sections. The questionnaire was given to 47 female students who were selected randomly to constitute the study sample. The researcher adopted the descriptive analytic approach, the suitable statistical methods, and the program of SPSS to analyze the study data. The findings of the research can be summed up in the following: 1-The rank of using the social media programs for learning process got the degree of sometimes. 2-The importance of using the social media programs in teaching got the degree of often. 3-The ways of activating the social media programs in learning process got the degree of seldom 4-There is no differences of statistical reference in the rank of using the social media programs in learning. This is attributed to the variable of level and major of study. 5-There is no differences of statistical reference in the importance of using the social media programs in learning. This is attributed to the variable of level and major of study. The study has come up with a number of recommendations. The most important of which are: -Spreading the culture of utilizing the social media programs is recommended among the educational community at Yemeni Universities. - There is a necessity to support the role of social media programs in order to enhance the quality of educational process at Yemeni Universities. -There is a suggestion to establish social media programs for the students of all Yemeni Universities or social media programs peculiar to every university. -There is a necessity to apply the ways of activating social media programs in learning process at Yemeni University in general and at Hadhramout University in particular.
Keywords: التعليم العالي -- تكنولوجيا التعليم -- مواقع التواصل الاجتماعي -- طلبة الجامعات